NILAI KEPEMIMPINAN DALAM BUKU PERIBAHASA BANJAR “BARUH URANG DIKARUNI, BARUH SAURANG TAUNG” KARYA Y.S. AGUS SUSENO (THE VALUE OF LEADERSHIP IN BANJAR'S BOOK OF PROVERBS “BARUH URANG DIKARUNI, BARUH SAURANG TAUNG” BY Y.S. AGUS SUSENO) - Aryadi, Aryadi; Dewi, Dwi Wahyu Candra; Chandra, Noor Eka (Universitas Lambung Mangkurat, 2024)
AbstractThe Value of Leadership In Banjar's Book of Proverbs “Baruh Urang Dikaruni, Baruh Saurang Taung” By Y.S. Agus Suseno. The study's overarching goal is to protect indigenous languages and cultures from extinction, with a focus on the Banjar language. Rising levels of globalization and modernity impacting all aspect of life, including cultural customs and traditions, which contributes to the problem. Leadership teachings from Banjar proverbs such as Baruh Saurang Taung and Baruh Urang Dikaruni by Y.S. Agus Suseno are the focus of this research. This qualitative descriptive study examines the significance of leadership through the lens of Y.S. Agus Suseno's books Baruh Urang Dikaruni, Baruh Saurang Taung. The results indicate that Baruh Saurang Taung Y.S. Agus Suseno's goal in writing Baruh Urang Dikaruni was to prevent the Banjar language from fading into oblivion.